Analysis of forest stands used by wintering woodland caribou in Ontario - Antoniak, K.; Cumming, H.G. (Rangifer, 1998)
Two summers' field surveys at 9 locations in northwestern Ontario showed that woodland caribou (Rangifer tarandus caribou) wintering areas supported jack pine and black spruce stands with low tree densities (mean 1552 trees/ ha, 39% of a fully stocked stand), low basal areas (mean 14.14 m2/ha), low volumes (mean 116 mVha, 68% of Normal Yield Tables) and short heights (95% of stands 12 m or less). Ecologically, most sights were classed V30. Significantly more lichen (averaging 39% lichen ground cover) was found on plots used by caribou. Three measured areas showed few shrubs, possibly enhancing escape possibilities and reducing browse attractive to moose. An HIS model predicted known locations of caribou winter habitat from FRI data with 76% accuracy. Landsat imagery theme 3 (open conifer) produced 74% accuracy. Combining these methods permitted prediction of all 50 test sites. The low volumes of timber found in caribou wintering areas suggest that setting aside reserves for caribou winter habitat would not sacrifice as much wood product value as might at first appear.